`Metered' aerosols of bronchodilator drugs in clinical trials: Influence of the method of administration - Cohen, Burton M. (1971)
Airway resistance, the volume of thoracic gas, and specific airway resistance were determined before and after administration of an isoproterenol-phenylephrine mist in random fashion to 20 patients with obstructive ventilatory disorders from a hand-triggered apparatus either used by the patient or given by the physician, and from a nebulizer automatically activated by patient inspiration. Specific airway resistance changes were the most sensitive guide to broncholytic effects. Maximal change followed exposure to the breath-activated unit, suggesting that its use in similar drug trials may reduce an important source of error in estimates of the efficacy of bronchopulmonary aerosols.